2006
DOI: 10.4049/jimmunol.177.7.4281
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Involvement of Tim-3 in the Regulation of Hepatic CD8+ T Cells in Murine Acute Graft-versus-Host Disease

Abstract: Tim-3, a member of the T cell Ig mucin (TIM) family regulates effector Th1 responses. We examined Tim-3 and its ligand expression as well as the effects of anti-Tim-3 mAb treatment in a murine model of acute graft-vs-host disease (aGVHD). In mice with aGVHD, Tim-3 expression was markedly up-regulated on splenic and hepatic CD4+ and CD8+ T cells, dendritic cells (DCs), and macrophages, and this was especially dramatic in hepatic CD8+ T cells. Both donor- and host-derived CD8+ T cells induced similar levels of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 41 publications
3
89
0
Order By: Relevance
“…Tim-3, as an important immune regulatory molecule, is expressed on effector Th1 cells and Tc1 cells (8)(9)(10)(11)(12)(13)(14), both of which play important roles in the immune response to HBV. However, whether Tim-3 plays a role in the development of HBV infection still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tim-3, as an important immune regulatory molecule, is expressed on effector Th1 cells and Tc1 cells (8)(9)(10)(11)(12)(13)(14), both of which play important roles in the immune response to HBV. However, whether Tim-3 plays a role in the development of HBV infection still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…As a ligand for Tim-3, galectin-9 is widely distributed in various tissues and is particularly abundant in the liver (29). Previous studies have shown that Tim-3-galectin-9 pathway modulates T cell secretion of IFN- (9,13,14), which is of particular importance to immunity against viral infection. Consistent with these reports, our data verified the simultaneous staining of Tim-3 and IFN- in CD8 + T cells ( Figures 2 and 4), which might explain why Tim-3 pathway influences IFN- production from CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of Tim3 inhibits the activity of Th1 cells and production of IFN-c, both of which play important roles in antitumor immunity [7,8]. Tim3, a transmembrane protein that contains an immunoglobulin-and a mucin-like domain, is expressed on many cells including Th1 cells, CD8 T-cells, monocytes, and dendritic cells [9][10][11][12]. Interaction of Tim3 with its ligands, phosphatidylserine and galectin-9, modulates the function of these cells [13,14].…”
Section: Introductionmentioning
confidence: 99%